The Impact of Youtube on Indonesian EFL Senior High School Student’s Motivation - Amethyst, Lidwina Mutiara Vita (PROJECT (Professional Journal of English Education), 2025)
This research investigates the impact of YouTube through the motivation of Indonesian senior high school students learning English as a Foreign Language (EFL). This research aims to offer insights for educators and students as a guide to develop educational content so that it can increase the motivation to learn. The methodology used was a quantitative approach, which involves 90 ten grade students from a senior high school in Indonesia. Data were collected through questionnaires that measure students' views on using YouTube for learning English and its effects on their motivation. The finding is to show that YouTube is an effective platform for increasing students' motivation to learn English by making the learning process more enjoyable and encouraging independent study. However, issues like unreliable content and distractions need to be addressed. By curating trustworthy materials and integrating YouTube into structured lessons, educators can enhance its effectiveness as a motivational learning resource. The author hopes to hear constructive feedback from the audience to enhance the quality of this research proposal.